Role of GABAAR in the Transition From Acute to Chronic Pain and the Analgesic Effect of Electroacupuncture on Hyperalgesic Priming Model Rats - Wang, Sisi; Du, Junying; Xi, Danning; Shao, Fangbing; Qiu, Mengting; Shao, Xiaomei; Liang, Yi; Liu, Boyi; Jin, Xiaomin; Fang, Jianqiao; Fang, Junfan (Frontiers in Neuroscience, 2021)
Chronic pain is a costly health problem that impairs health-related quality of life when not effectively treated. Regulating the transition from acute to chronic pain is a new therapeutic strategy for chronic pain that presents a major clinical challenge. The underlying mechanisms of pain transition are not entirely understood, and strategies for preventing this transition are lacking. Here, a hyperalgesic priming model was used to study the potential mechanism by which γ-aminobutyric acid receptor type A (GABAAR) in the dorsal root ganglion (DRG) contributes to pain transition. Furthermore, electroacupuncture (EA), a modern method of acupuncture, was administered to regulate pain transition, and the mechanism underlying EA’s regulatory effect was investigated. Lower expression of GABAAR in the lumbar DRG was implicated in pain transition. In addition, GABAAR may be involved in Protein Kinase C epsilon (PKCε) activation in the DRG. EA considerably increased the mechanical pain thresholds of hyperalgesic priming model mammals in both the acute and chronic phases. Furthermore, EA upregulated the expression of GABAAR and inhibited the activation of PKCε in the DRG. In addition, peripheral administration of picrotoxin blocked the analgesic effect of EA on the model rats and abolished the regulatory effect of EA on PKCε activation. These findings suggested that GABAAR plays a key role in both the transition from acute to chronic pain and the analgesic effect of EA on hyperalgesic priming.